Relationship of Sleep Quality and Oxidative Stress Level in Smartphone Users; Study in Faculty of Medicine Student, Universitas Baiturrahmah - Malik, Rifkind; Rafli, Rhandyka; Salmi, Salmi; Noer, Yasinta Allisya (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Excessive smartphones can affect sleep quality, reducing sleep duration. This lack of sleep will impact various health and increase levels of free radicals in the body, affecting various cell functions. AIM: The aim of the study was to measure the relationship between sleep quality due to smartphone use and serum malondialdehyde (MDA) levels. MATERIALS AND METHODS: This was a quasi-experimental with pre- and post-test group study. Sleep quality was assessed with Pittsburgh Sleep Quality Index (PSQI), and the smartphone addiction was assessed based on Smartphone Addiction Scale (SAS) score. The subjects were divided into four groups (n = 6) based on their PSQI and SAS score. The first group was the subjects with normal sleep and non-smartphone addict. The second group was the subjects with normal sleep but smartphone addict. The third group was the subjects with abnormal sleep and non-smartphone addict. Furthermore, fourth was the subjects with abnormal sleep and smartphone addiction. All the subjects were asked to sleep usually and used the smartphone as necessary a day before the study started. Blood plasma was collected from the subject before and after the study for MDA measurement. Plasma MDA was determined using the thiobarbituric acid test. RESULTS: Smartphone use can reduce sleep quality and duration, resulting in sleep deprivation. There was no increase in MDA concentration (p > 0.05) in the ordinary and non-addictive or smartphone-addicted sleep group. Meanwhile, the group that stayed up late and was neither addictive nor addictive showed an increase in MDA levels and was statistically significant (p < 0.05). CONCLUSION: Adequate sleep can reduce blood serum MDA levels and smartphone use does not affect MDA levels.